2012
DOI: 10.1289/ehp.1104051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Decabrominated Diphenyl Ether (PBDE-209) in Regulation of Growth and Apoptosis of Breast, Ovarian, and Cervical Cancer Cells

Abstract: Background: Polybrominated diphenyl ethers (PBDEs), commonly used in building materials, electronics, plastics, polyurethane foams, and textiles, are health hazards found in the environment.Objective: In this study we investigated the effects of PBDE-209, a deca-PBDE, on the regulation of growth and apoptosis of breast, ovarian, and cervical cancer cells as well as the underlying protein alterations.Methods: We used MCF-7 and MCF-7/ADR (multidrug-resistant MCF-7) breast cancer cell lines, the HeLa cervical can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 42 publications
5
52
0
Order By: Relevance
“…They showed that phosphorylation of ERK1/2 is increased by IGF-1 and this increase is constantly high after 60 minutes. Similar pattern for ERK phosphorylation has been reported in response to some chemicals other than growth factors [45].…”
Section: Discussionsupporting
confidence: 83%
“…They showed that phosphorylation of ERK1/2 is increased by IGF-1 and this increase is constantly high after 60 minutes. Similar pattern for ERK phosphorylation has been reported in response to some chemicals other than growth factors [45].…”
Section: Discussionsupporting
confidence: 83%
“…This may explain why COX expression is not entirely dependent on ROS formation in the present study. Although there are limited studies on PBDE effects on cellular signaling pathways, it is reported that a commercial PBDE mixture DE-71 and PBDE congeners such as BDE-47, 77, 99, and 209 stimulates PKC translocation, PKC phosphorylation, and ERK phosphorylation in vitro (Fan et al , 2010; Li et al , 2012; Madia et al , 2004). Further investigation on the interactions among kinase signaling pathways, transcription factors, and prostaglandin pathways will lead us toward a better understanding of the mechanisms associated with PGE2 production and COX expression stimulated by BDE-47 in gestational compartments.…”
Section: Discussionmentioning
confidence: 99%
“…nervous system (Dingemans et al, 2011), the liver, reproduction and development (Li et al, 2012) and the endocrine system Ren and Guo, 2012;Li et al, 2013;Ren and Guo, 2013). Although there is limited information on the immunotoxicity of PBDEs, recent animal investigations indicate suppressive effects of PBDEs on the immune system.…”
Section: Introductionmentioning
confidence: 99%